U.S. Naval Oceanographic Office Charting of the Antarctic - Fowler, Charles E.; Moore, Harry H. (The International Hydrographic Review, 2015)
U.S. Naval Oceanographic Office nautical and aeronautical charting efforts in the Antarctic and surrounding waters are described from the United States Exploring Expeditions (1838-1842) to the present. Charting programs, and requirements for the Byrd expeditions, Operation High-jump, Operation Windmill, and Deep Freeze Operations that have continued annually since 1955, are also reviewed. Illustrations are included showing past and present nautical chart coverage of the Antarctic.